Blocking NMDA-Receptors in the Pigeon’s Medial Striatum Impairs Extinction Acquisition and Induces a Motoric Disinhibition in an Appetitive Classical Conditioning Paradigm - Gao, Meng; Pusch, Roland; Güntürkün, Onur (Frontiers in Behavioral Neuroscience, 2019)
The medial striatum of birds resembles the mammalian dorsal striatum, which plays a key role in the extinction of learned behavior. To uncover the variant and invariant neural properties of extinction learning across species, we use pigeons as an animal model in an appetitive extinction paradigm. Here, we targeted a medial sub-region of the pigeon’s striatum that receives executive, visual and motor pallial projections. By locally antagonizing the N-methyl-D-aspartate (NMDA) receptors through 2-Amino-5-phosphonovalerianacid (APV) during extinction, we observed an unspecific disinhibition effect, namely an increase in conditioned pecking to a rewarded control stimulus. In addition, blocking the NMDA receptors substantially deteriorated the extinction acquisition, implying that the pigeons still responded vigorously to the CS- even without food reward during extinction. After correcting for the unspecific effect of APV, the impaired extinction acquisition remained significant, which leads to the assumption that the delayed extinction effect is possibly caused by deficits in the updating of value coding of altered reward contingencies. Also, the APV-induced disinhibition seems to result from local hyperactivity that primarily drives actions towards cues of high appetitive value. The overall correspondence of our results with those from mammals suggests common neural substrates of extinction and highlights the shared functionality of the avian and mammalian dorsal striatum despite 300 million years of independent evolution.